First Aid Training For Divers In Watu Ulo Village - Ely Rahmatika Nugrahani; Zuhrotul Eka Yulis Anggraeni; Desinta Putri Ambarsari; Rijal Maulana Juan Alkautsar; Vinda Anayu Aprilia; Anisatus Syamsil Arifin (Jurnal Pengabdian Indonesia, 2024)
Health problems among divers in Watu Ulo Hamlet were increased incidence of emergencies in divers and the absence of a first aid training program for emergency diving incidents. The first aid training program for fishermen used the roleplay method is one program that can be attempted to prevent death. This program collaborates with the Sumberejo Village apparatus consisting of the Head of Watu Ulo Hamlet and the Head of the Payangan Beach Diver's Association. The methods used to achieve these goals are 1) situation analysis, 2) preparation, 3) training, and 4) evaluation and assistance to fishermen to see the suitability of the problem with the alternative solutions provided. The training results showed that 75% of fishermen experienced increased knowledge, 60% increased attitudes, and 85% experienced increased skills and expressed satisfaction with holding first aid training activities for fishermen's emergencies using the role-play method.kesehatan pada penyelam di Dusun Watu Ulo yaitu meningkatnya kejadian kegawatdaruratan pada penyelam dan belum adanya program pelatihan pertolongan pertama pada kejadian kegawatdaruratan penyelaman. Program pelatihan pertolongan pertama pada nelayan dengan metode role play merupakan salah satu program yang dapat diupayakan untuk mencegah kematian. Program ini bekerja sama dengan perangkat Desa Sumberejo yang terdiri dari Kepala Dusun Watu Ulo dan Ketua Ikatan Penyelam Pantai Payangan. Metode yang digunakan untuk mencapai tujuan tersebut yaitu 1) analisis situasi, 2) persiapan, 3) pelatihan, dan 4) evaluasi serta pendampingan kepada nelayan untuk melihat kesesuaian masalah dengan alternatif pemecahan yang diberikan. Hasil pelatihan menunjukkan bahwa 75% nelayan mengalami peningkatan pengetahuan, 60% mengalami peningkatan sikap, dan 85% mengalami peningkatan keterampilan serta menyatakan puas terhadap terselenggaranya kegiatan pelatihan pertolongan pertama pada kegawatdaruratan nelayan dengan metode role play.